PROMOTING LEARNER AUTONOMY THROUGH SELF-ASSESSMENT IN WRITING CLASS - Muhammad Islakhul Huda; Siti Musarokah; Andreas Bambang Prabowo Kusumo Adi (Universitas PGRI Semarang, 2020)
In the 2020 era, the corona pandemic has caused many impacts throughout the country that are very broad in all fields, including education. Learners and lecturers are no exception affected by the pandemic, and always strive to be able to carry out teaching and learning activities that can cover deficiencies in the field. Based on the current complex learning and living background, this article discuss the autonomous learning mode of College English learners, puts forward the discussion of constructing strategy from self-assessment to improve autonomous learning mode of college English in writing classess. In discussing this article, the writer used theoretical review and qualitative document methods which were observations, data collection, data processing, revisions, and documentation. Then, it can be concluded that the results of research on self-assessment can improve learner autonomy so that learners can get the ease from online writing classes during the pandemic and in the future from direct methods (face to face) learning more beneficially